Contrasting mechanisms of de novo copy number mutagenesis suggest the existence of different classes of environmental copy number mutagens. (6th August 2015) - Conover, Hailey N.; Argueso, Juan Lucas
Abstract : While gene copy number variations (CNVs) are abundant in the human genome, and often are associated with disease consequences, the mutagenic pathways and environmental exposures that cause these large structural mutations are understudied relative to conventional nucleotide substitutions in DNA. The members of the environmental mutagenesis community are currently seeking to remedy this deficiency, and there is a renewed interest in the development of mutagenicity assays to identify and characterize compounds that may induce de novo CNVs in humans. To achieve this goal, it is critically important to acknowledge that CNVs exist in two very distinct classes: nonrecurrent and recurrent CNVs. The goal of this commentary is to emphasize the deep contrasts that exist between the proposed pathways that lead to these two mutation classes. Nonrecurrent de novo CNVs originate primarily in mitotic cells through replication‐dependent DNA repair pathways that involve microhomologies (<10 bp), and are detected at higher frequency in children of older fathers. In contrast, recurrent de novo CNVs are most often formed in meiotic cells through homologous recombination between nonallelic large low‐copy repeats (>10, 000 bp), without an associated paternal age effect. Given the biological differences between the two CNV classes, it is our belief that nonrecurrent and recurrent CN mutagens will probably differ substantially in their modes of action. Therefore, each CNV class may require their own uniquely designed assays, so that we as a field may succeed in uncovering the broadest possible spectrum of environmental CN mutagens. Environ. Mol. Mutagen. 57:3–9, 2016. © 2015 Wiley Periodicals, Inc.